Párizs és Varsó, 1918 - 1922 = Paris and Warsaw 1918 - 1922 - Majoros, István (Közép-Európai Közlemények, 2017)
Poland was a member state of the French system of alliance in the interwar period. We can divide the Franco-Polish relations between 1918 (the proclamation of the Polish independence) and 1939 (the attack of Poland by Germany) into three parts: a) the fi rst part from the end of the First World War to Locarno is the creation of the alliance between the two countries. b) from Locarno to 1938: the period of the distrust for Poland, so Warsaw is approching to Berlin. For this reason Paris is distrustful against Warsaw. c) from the automne 1938 to September 1939, the two countries will again fi nd each other, but this is the endgame, because 1st September 1939 Germany attacks Poland. The present study deals with the fi rst periode from 1915 to the signature of the Franco-Polish political and military alliance in 1921 and 1922. The author used French archival resources to write this work.